Impact of non-Newtonian fluid behavior on hydrodynamics and mass transfer in spacer-filled channels. (26th November 2020) - Fischer, N; Masoudian, M; Germann, N
Abstract: Spiral wound membrane modules operate as filtration modules in the food, beverage, and pharmaceutical industries. As many fluids are non-Newtonian or become non-Newtonian during concentration, it is essential to gain an understanding of the effect of a shear-rate dependent viscosity. This computational work examines the impact of the fluid rheology and the Reynolds number on the hydrodynamics and the mass transfer in zigzag and cavity spacer-filled channels under laminar flow conditions. To describe the rheology of the working fluid, we utilized the well-known power-law model. The power-law index values corresponded to 0.7, 1, and 1.3, representing shear-thinning, Newtonian, and shear-thickening behavior, respectively. The Reynolds number was varied up to 160 whereas the Schmidt number was kept constant at 500. A standard convection–diffusion equation with a constant wall concentration was employed to describe the mass transfer. In agreement with previous works on Newtonian fluids, the zigzag spacer was found to be the most promising spacer type, because of the enhanced mass transfer in the reattachment regions. Whereas the mass transfer was only slightly affected by the rheology, the shear thinning fluid produced the smallest pressure drop. As a direct consequence of the positive effect on the pressure drop, the spacer efficiency was highest in all configurations. The results of this first numerical investigation in the context of non-Newtonian fluid flow through spacer-filled channels emphasize the importance of taking into account a varying fluid viscosity in the design and operation of the filtration process.